Pesan Dakwah dalam Novel Bumi Cinta Karya Habiburrahman El Shirazy - Syafriwaldi Syafriwaldi (IAIN Batusangkar, 2022)
Novels are one of the da'wah media that can be used by Da'i to influence mad'u to carry out what has become a provision or rule in Islam. One of the Da'i who made novels as a medium of da'wah is Habiburrahamn El Shirazy. He is a scholar, preacher, and writer who has produced phenomenal works that relate daily life to Islamic da'wah. In this study, the author examines a novel written by Habiburrahamn El Shirazy by entitled Bumi Cinta. The novel Bumi Cinta tells about the struggle of a salaf santri named Muhammad Ayyas in defending his faith from people who do not believe in God, as well as people who are very anti-Islam in the city of Moscow, Russia. This research is a qualitative research using content analysis techniques. The researcher categorizes the message of da'wah in this novel by using the theory of da'wah message. The results of this study are that the expelled novel contains messages related to faith, worship, muamalah and morality.